ANALISIS DIMENSI PROFIL PELAJAR PANCASILA PADA KEGIATAN EKSTRAKURIKULER PRAMUKA PENGGALANG DI SDN SENDANGMULYO 02 - Rahmawati, Alfina Ika Putri; Sumarno, Sumarno (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to determine the implementation of the dimensions of the Pancasila Student Profile in extracurricular activities for scouts. This type of research is qualitative research in descriptive form. This research was carried out at SDN Sendangmuyo 02, Tembalang District, Semarang. The subject of this research is the scoutmaster for class V and VI. The instruments used by researchers to collect data are interviews, observation and documentation. Based on the results of research conducted by researchers, it shows that the implementation of the Pancasila Student Profile in the extracurricular activities of the scout raisers at SDN Sendangmulyo 02 carried out by the scout supervisor followed by classes V and VI shows four dimensions of the Pancasila Student Profile. .In its implementation, the scoutmaster together with all the scoutmaster participants in classes V and VI carry out prayer activities (the dimension of faith, devotion to God Almighty, and having noble morals), ceremonial and singing activities (the dimension of global diversity), semaphore activities (the independent dimension ), and question and answer activities on material in the Penggalang SKU book (critical reasoning dimensions). From the habituation activities applied to the scouts, the scouts can form the scouts to have high religious values, foster a sense of love for the homeland, train independence, and sharpen the brain to get used to answering questions with critical reasoning.